Clinical and epidemiological characteristics of herpes zoster at a tertiary care center compared to population-based data: a ten-year retrospective cohort study - Johanna Lenz; Hans Helmut Niller; Sebastian Haferkamp (BMC Infectious Diseases, 2026)
Abstract Background Herpes zoster (HZ) results from reactivation of the latent varicella-zoster virus (VZV) and may cause severe pain and serious complications. The risk increases with age, immunosuppression, and certain chronic conditions. Tertiary care centers disproportionately treat patients with such risk profiles, yet data comparing tertiary care populations with population-based cohort studies are limited. This study aimed to provide a comprehensive clinical and epidemiological characterization of HZ patients at a tertiary care center and to compare findings with those from population-based studies. Methods All patients at the University Hospital Regensburg with an HZ diagnosis (ICD code B02*) between January 2014 and December 2023 were included and subsequently underwent manual chart review for clinical validation and data extraction, yielding 786 cases in 780 patients. We analyzed patient demographics, comorbidities, immunosuppression, anatomical location, complications, hospitalization status, and vaccination status. Results Of 786 cases, 398 occurred in women and 388 in men, with a median age of 60 years. A total of 13.5% of cases were classified as immunocompromised. The trigeminal nerve was involved in 50.1% of cases, and herpes zoster ophthalmicus (HZO) was present in 41.3%. Most cases, 72.8%, proceeded without complications, with postherpetic neuralgia (PHN) being the most common complication, affecting 8.4% of cases. The hospitalization rate was 57.6%, and HZ vaccination status was documented in fewer than 1% of cases. Conclusions Compared to published population-based studies, this cohort showed an increased risk profile for severe disease course as immunocompromised patients and cranial manifestations were markedly overrepresented. Despite that, the complication rate was comparable. Early intravenous antiviral therapy during hospitalization may have contributed to this, though retrospective design precludes causal inference. Prospective studies are needed to confirm this hypothesis. The near-total absence of vaccination records indicates a significant documentation gap and underscores the need for systematic vaccination counselling and documentation in tertiary care centers.